The teaching of school mathematics in the context of Countryside Education: reflections from official documents - Valdomiro Pinheiro Teixeira Junior; Márcio de Sousa Gomes (Universidade Federal do Norte do Tocantins, 2021)
This research seeks to reflect on the potential and implications of three of the six principles indicated in the References for a National Countryside Education Policy (2004), and that emerge from educational documents on the countryside Education policy in the teaching of School math. The methodological procedures adopted are based on the documentary analysis of educational policy, in this specific case, those dealing with education built by rural populations. We start from the following problem: What are the potentials and implications of the incidence of rural education principles in the teaching of school mathematics? The research allowed an expansion of the discussions raised by the Movement for Countryside Education, signaling that the possible implications of the incidence of the principles of Countryside Education in the teaching of school Mathematics, are mainly in the relationship between formal mathematical content and peasant reality, already the potential of this incidence is found in the possibility of school education linked to an emancipatory project.